THE SECURITISATION OF TIBETAN BUDDHISM IN COMMUNIST CHINA - Tsering Topgyal (Politikologija religije, 2012)
This article examines the troubled relationship between Tibetan Buddhism and the Chinese state since 1949. In the history of this relationship, a cyclical pattern of Chinese attempts, both violently assimilative and subtly corrosive, to control Tibetan Buddhism and a multifaceted Tibetan resistance to defend their religious heritage, will be revealed. The article will develop a security-based logic for that cyclical dynamic. For these purposes, a two-level analytical framework will be applied. First, the framework of the insecurity dilemma will be used to draw the broad outlines of the historical cycles of repression and resistance. However, the insecurity dilemma does not look inside the concept of security and it is not helpful to establish how Tibetan Buddhism became a security issue in the first place and continues to retain that status. The theory of securitisation is best suited to perform this analytical task. As such, the cycles of Chinese repression and Tibetan resistance fundamentally originate from the incessant securitisation of Tibetan Buddhism by the Chinese state and its apparatchiks. The paper also considers the why, how, and who of this securitisation, setting the stage for a future research project taking up the analytical effort to study the why, how and who of a potential desecuritisation of all things Tibetan, including Tibetan Buddhism, and its benefits for resolving the protracted Sino-Tibetan conflict.